Magnetic field Under Overhead Power Lines - HOUICHER SALAH EDDINE (University Of Eloued جامعة الوادي, 2020)
With the development of electrical energy networks, environmental impact assessment in the neighbourhood and high voltage overhead power lines caused public concern. This paper presents a simulation methodology for analyze the distribution of the magnetic field generated by high voltage overhead transmission line. The effect of sag due to the weight of the line on the values of the magnetic field on ground level has also been discussed. The analytical results of the calculation of a 400 KV line based on image method using MATLAB numerical software which makes it possible to better analyze and to represent the transverse profile of the magnetic field under the power line.
Intervention
Keywords: overhead power line; high voltage; magnetic field; sag; simulation